Review paperAmorolfine vs. ciclopirox – lacquers for the treatment of onychomycosis - Tabara, Katarzyna; Szewczyk, Anna E.; Bienias, Wojciech; Wojciechowska, Agnieszka; Pastuszka, Marta; Oszukowska, Magdalena; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Amorolfine 5% and ciclopirox 8% nail lacquers are commonly used in topical treatment of onychomycosis. These formulations may be used alone or in combination with oral antifungal agents. Amorolfine and ciclopirox are valuable therapeutic options, however, their usage in monotherapy should be limited. Proper amorolfine and ciclopirox penetration through the nail plate is provided by transungual drug delivery systems. Although amorolfine and ciclopirox have a different mode of action, they both exhibit a broad antifungal activity. The use of antifungal nail lacquers in combination with oral agents, such as terbinafine and itraconazole, improves efficacy of antifungal therapy.